2006
DOI: 10.1002/app.25212
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of radical polymerization. VII. Investigation into the solution copolymerization of acrylonitrile and itaconic acid by real‐time 1H NMR spectroscopy

Abstract: Free radical solution copolymerization of acrylonitrile (AN) and itaconic acid (IA) was performed with DMSO-d 6 as the solvent and 2,2 0 -azobisisobutyronitrile (AIBN) as the initiator. Weight ratio of the monomers to solvent and molar ratio of initiator to monomers were constant in all experiments. The initial comonomer composition was the only variable in this study. On-line 1 H NMR spectroscopy was applied to follow individual monomer conversion. Mole fraction of AN and IA in the reaction mixture (f) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The group of Mahdavian has studied AM homopolymerization in aqueous solution [28] as well as various copolymerization in organic solution. [37][38][39][40] Three criteria for running in-situ NMR experiments were reported: [28] 1) a reaction rate that is less than the scanning rate, 2) solubility of the polymer in the solvent, and 3) distinguishable monomer/ polymer peaks so that monomer composition and conversion can be determined. A fourth criterion, namely that isothermal conditions are maintained, should be added.…”
Section: Introductionmentioning
confidence: 99%
“…The group of Mahdavian has studied AM homopolymerization in aqueous solution [28] as well as various copolymerization in organic solution. [37][38][39][40] Three criteria for running in-situ NMR experiments were reported: [28] 1) a reaction rate that is less than the scanning rate, 2) solubility of the polymer in the solvent, and 3) distinguishable monomer/ polymer peaks so that monomer composition and conversion can be determined. A fourth criterion, namely that isothermal conditions are maintained, should be added.…”
Section: Introductionmentioning
confidence: 99%
“…On‐line 1 H NMR has also been used in different kinetic studies by several authors 451–454. A series of studies of the radical polymerization of STY/itaconic acid and acrylonitrile/itaconic acid using this technique were also carried out 455–459. Landfester et al456 demonstrated that it is feasible to use on‐line solid‐state 1 H‐ and 13 C NMR spectroscopy in the study of emulsion polymerization of BA.…”
Section: On‐line Sensors For Polymer Property Trajectory Monitoringmentioning
confidence: 99%
“…Several methods have been followed to improve their hydrophilic properties, such as coating, adsorption, surface plasma treatment, surface hydrolysis, surface graft polymerization and chemical modification 1–4. Various vinyl and acrylic monomers, have been reported as a comonomer to modify PAN properties 5–7. Ulbricht et al4 introduced carboxylic groups by grafting acrylic acid under pure helium plasma, whereas Zhao et al8 used argon plasma for the grafting in PAN.…”
Section: Introductionmentioning
confidence: 99%